Examining the feasibility of waqf (Islamic endowment)-based takāful model from the Malaysian legal perspective - Megat Laksana, Nan Noorhidayu; Che Mohd Salleh, Marhanum; Che Embi, Nor Azizan (IIUM Press, 2020)
In 2004, the State Islamic Religious Council (SIRC) in Malaysia stated their concern on jurisdiction pertaining to control of state waqf assets, which were different among the states in Malaysia. Based on discussions with the legal experts, they have proposed the adoption of the agency principle in order to cater to the issue of control over the waqf fund. This study discusses the feasibility of waqf (Islamic endowment)-based takāful products to be practiced in Malaysia by considering the opinions of SIRC and legal experts in the industry. In order to achieve the research objective, this research adopts a qualitative methodology and focus group discussions with the SIRC representatives and legal experts. Overall, it is found that all respondents have agreed with the proposed waqf-based takāful model as it has special values that may inculcate the culture of brotherhood in society as this concept encourages people to give something to others without receiving any financial return. This study contributes to the discussion of the feasibility of waqf (endowment) principle to be introduced in the takāful products from the legal perspective.